Gut and Vagina Microbiota Associated With Estrus Return of Weaning Sows and Its Correlation With the Changes in Serum Metabolites - Zhang, Jia; Liu, Min; Ke, Shanlin; Huang, Xiaochang; Fang, Shaoming; He, Maozhang; Fu, Hao; Chen, Congying; Huang, Lusheng (Frontiers in Microbiology, 2021)
More and more studies have indicated that gut microbiota takes part in the biosynthesis and metabolism of sex hormones. Inversely, sex hormones influence the composition of gut microbiota. However, whether microbiota in the gut and vagina is associated with estrus return of weaning sows is largely unknown. Here using 16S rRNA gene sequencing in 158 fecal and 50 vaginal samples, we reported the shifts in the gut and vaginal microbiota between normal return and non-return sows. In fecal samples, Lactobacillus and S24-7 were enriched in normal return sows, while Streptococcus luteciae, Lachnospiraceae, Clostridium, and Mogibacterium had higher abundance in non-return sows. In vaginal swabs, the OTUs annotated to Clostridiales, Ruminoccaceae and Oscillospira were enriched in normal return sows, while those OTUs annotated to Campylobacter, Anaerococcus, Parvimonas, Finegoldia and Dorea had higher abundances in non-return sows. Co-abundance group (CAGs) analysis repeated the identification of the bacterial taxa associated with the estrus return of weaning sows. The predicted functional capacities in both gut and vaginal microbiome were changed between normal return and non-return sows. Serum metabolome profiles were determined by non-targeted metabolome analysis in seven normal return and six non-return sows. The metabolite features having higher abundance in normal return sows were enriched in the pathways steriod hormone biosynthesis, starch and sucrose metabolism, galactose metabolism and vitamin B6 metabolism, while the metabolite features belonging to organic acids and derivatives, indoles and derivatives, sulfoxides, and Lignans and neolignans had significantly higher abundance in non-return sows. Correlation analysis found that the changes of gut microbiota were associated with the shifts of serum metabolites, and suggested that certain bacteria might affect estrus return of weaning sow through serum metabolites. These findings may provide new insights for understanding the role of the gut and vaginal microbiota in sow return to estrus after weaning.